International relations and historical sociology : breaking down boundaries - Hobden, Stephen, 1956- (Routledge advances in international relations and politics ;, 1998)
This book provides an original analysis of recent work by key historical sociologists through the prism of International Relations. Stephen Hobden investigates the number of issues which overlap between the two disciplines by focusing on three main themes: * the ways in which historical sociologists approach international relations in general and the concept of an international system in particular * recent advances on the concept of the state as developed by Historical Sociology and their implications for International Relations * the potential for productive dialogue between the.